Investing in orphan crops to improve food and livelihood security of Uganda’s rural poor - Naluwairo, Ronald (Advocates Coalition for Development and Environment ACODE, 2011)
This policy research paper is an analysis of the extent to which Uganda’s food and agricultural-related policies and policy frameworks support the production and wider use of orphan crops in national development. Its major objective is to provide policy recommendations that can be adopted to support the production, conservation and wider use of orphan crops for enhanced food and livelihood security, particularly of Uganda’s rural poor.